Does Online Comprehension Monitoring Make a Unique Contribution to Reading Comprehension in Beginning Readers? Evidence from eye movements. (3rd September 2018) - Kim, Young-Suk Grace; Vorstius, Christian; Radach, Ralph
ABSTRACT: The goal of this study was to investigate the nature of online comprehension monitoring, its predictors, and its relation to reading comprehension. Questions were concerned with (a) beginning readers' sensitivity to inconsistencies, (b) predictors of online comprehension monitoring, and (c) the relation of online comprehension monitoring to reading comprehension over and above word reading and listening comprehension. Using eye tracking technology, online comprehension monitoring was measured as the amount of time spent rereading target implausible words and looking back at surrounding contexts. Results from 319 second graders revealed that children spent greater time fixating on inconsistent than consistent words and engaged in more frequent lookbacks. Comprehension monitoring was explained by both word reading and listening comprehension. However, comprehension monitoring did not uniquely predict reading comprehension after accounting for word reading and listening comprehension. These results provide insight into the nature of comprehension monitoring and its role in reading comprehension for beginning readers.